LEARNING THROUGH THE EVERYDAY EXPERIENCES OF BIOLOGICAL / FOSTER PARENTING - Bagdonaitė-Stelmokienė, Ramunė; Žydžiūnaitė, Vilma (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Learning through everyday experiences is understood as a complex process during which the learner undergoes various social interactions; it is an emotional, cognitive and behavioural process of learning. The aim of the study was to describe the process of learning of parents and foster parents through the everyday experiences of biological/foster parenting by revealing the similarities and differences of their experiences. The article presents the findings of the qualitative research. Applying the narrative interview, 4 parents and 8 foster parents were interviewed in the study. The data were analysed by using an inductive qualitative content analysis method. The findings revealed that the personal change of parents and foster parents and their growth in parenthood takes place in the process of learning from everyday experiences. The birth of a child into a family as well as the acceptance of a non-relative child into a foster family pose a number of challenges and cause confusion, but it is the experience of giving, joy and community too. The most striking difference between biological and foster parenting is revealed through the experience of ‘emotional triangle’ which is the only characteristic of foster parents. Communication with the foster child’s biological family is one of the most complex aspects of foster parenting.